The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1523/jneurosci.14-07-04338.1994
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of retinal ganglion cells innervating the cat's geniculate wing: an in vitro study

Abstract: We have examined in vitro the morphology and visual response properties of retinal ganglion cells innervating a component of the cat's lateral geniculate nucleus known as the geniculate wing (or retinorecipient zone of the pulvinar). Ganglion cells were first labeled in situ by retrograde transport of fluorescent microspheres from the geniculate wing. Labeled cells were injected intracellular with Lucifer yellow and biocytin in the isolated retina and visualized immunohistochemically. With one exception, stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(105 citation statements)
references
References 55 publications
7
101
0
Order By: Relevance
“…These 3 morphological types of ganglion cells, α-, β-, and γ-cells corresponded to the physiologically defined groups of Y-, X-, and W-cells, respectively [4,15,38]. So far, RGCs have been divided into 3 major types in most mammals, but it is probable that they could be classified more precisely [25,29,36].…”
Section: Intracellular Filling With Lucifer Yellow (Ly)mentioning
confidence: 95%
“…These 3 morphological types of ganglion cells, α-, β-, and γ-cells corresponded to the physiologically defined groups of Y-, X-, and W-cells, respectively [4,15,38]. So far, RGCs have been divided into 3 major types in most mammals, but it is probable that they could be classified more precisely [25,29,36].…”
Section: Intracellular Filling With Lucifer Yellow (Ly)mentioning
confidence: 95%
“…Several other anatomical types have coverage factors greater than two (Rodieck 1998;Wässle and Boycott 1991), and even as large as six (Berson 2003;Pu et al 1994). In a recent anatomical classification of rabbit ganglion cells, Rockhill et al (2002) found that their 13 morphological types needed to have an average coverage factor of 3.2 to account for the ganglion cell density that they measured.…”
Section: Introductionmentioning
confidence: 99%
“…Subsets of mammalian ganglion cell classes project to an array of central targets (Fukuda and Stone, 1974;Farmer and Rodieck, 1982;Leventhal et al, 1985;Rodieck and Watanabe, 1993;Pu et al, 1994;Rodieck, 1998), but a unified description of all classes and distributions in the ganglion cell layer has remained elusive. Several summaries of how neuronal typologies might be abstracted have emerged, some accompanied by debates regarding methods, definitions, and results (Rowe and Stone, 1977;Hughes, 1979;Holden, 1981;Rodieck and Brening, 1982;Famiglietti, 1992;Wingate et al, 1992;Cook, 1998;Masland and Raviola, 2000).…”
mentioning
confidence: 99%